Perceptions, maltreatment and religion as predictors of the psycho-emotional impact on nurses during the COVID-19 pandemic - Jhon Alex Zeladita-Huaman; Stefanny Lizbeth De la Cruz-Espinoza; Gabriela Samillán-Yncio; Rosa Castro-Murillo; Eduardo Franco-Chalco; Roberto Zegarra-Chapoñan (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to analyze the relationship between perceptions, abuse and religion with the psycho-emotional impact on nurses during the COVID-19 pandemic. Methods: descriptive-analytical cross-sectional study. It took place between 2020 and 2021 and a total of 319 clinical nurses in Peru were interviewed using the DASS-21. Associations were assessed using Spearman's Rho and multiple regression. Results: 18.5% had some degree of stress; 50.2%, anxiety and 29.1%, depression. Experience of abuse, self-perception of mental health and religion were predictors of stress, anxiety and depression. The length of work experience predicts stress and anxiety. In addition, self-perception of information and gender were predictors of depression. Conclusions: peruvian nurses have high levels of stress, anxiety and depression, and this psycho-emotional impact was associated with perceptions, experiences of abuse and religion.